Lack of evidence of human papillomavirus-induced squamous cell carcinomas of the oral cavity in southern Germany - Reuschenbach, Miriam; Kansy, Julia Katharina; Garbe, Kira; Vinokurova, Svetlana; Flechtenmacher, Christa; Tóth, Csaba; Prigge, Elena-Sophie; Thiele, Oliver C.; Reinert, Siegmar; Hoffmann, Jürgen; Knebel Doeberitz, Magnus von; Freier, Kolja (Oral oncology, 2013)
Objectives - The aim of the present study was to identify HPV-attributable SCC of the oral cavity (OSCC) in a cohort of patients from southern Germany. - Materials and methods - A sensitive PCR-enzyme immunoassay (EIA) was followed by a more specific in situ hybridization (ISH) to detect high risk human papillomavirus (HPV). An immunohistochemical dual-staining for p16INK4a and the proliferation marker Ki-67 was used to assess whether co-expression of p16INK4a/Ki-67 is a better surrogate marker for HPV in OSCC than p16INK4a alone, based on the hypothesis that combined p16INK4a and Ki-67 expression might specifically discriminate oncogene-induced p16INK4a expression from cell-cycle arrest-inducing senescence-associated p16INK4a expression. - Results - HPV-DNA by PCR-EIA could be detected in 25.1% (69/275) of the tumors, but ISH was negative in all of them. Diffuse p16INK4a overexpression was detected in 11 HPV PCR-positive tumors, but also in 6 HPV PCR-negative tumors. p16INK4a-expressing cells in diffusely positive tumors co-expressed Ki-67, irrespective of the HPV status. Neither the sole HPV status nor combined HPV/p16INK4a status nor the sole p16INK4a status was significantly associated with disease free or overall survival, however a trend towards better overall survival of patients whose tumor expressed p16INK4a in a focal pattern (=p16INK4a-positive/Ki-67-negative cells) compared to no p16INK4a expression (p=0.09) was observed. - Conclusion - Viral DNA can be detected in some tumors by a sensitive PCR, but absence of ISH signals indicates that the HPV-attributable fraction is smaller than estimated from PCR positivity. p16INK4a/Ki-67 co-expression is detectable in a fraction of OSCC irrespective of the HPV status.